The determinants of reading on self-motivation among users in academic library: a conceptual framework / Syaiful Hisyam Saleh ... [et al.] - Saleh, Syaiful Hisyam; Nordin, Norhazlan; Mohamed Shuhidan, Shamila; Husaini, Haslinda (Faculty of Information Management, 2022)
Reading is a crucial skill because it influences one's intellectual and emotional growth. Reading is a habit that a person develops to broaden their perspective on the world via personal experience, and it can result in enlightened self-discovery. Malaysians read, on average, just two novels a year, which is still less than the world average. Those who can read well have a greater chance of widening their mental horizons and achieving success. However, due to digital transformation, majority of Malaysian university students have reading difficulties. Although they can read, they would rather not. Therefore, this paper aims to propose the framework of reading factors that influenced on selfmotivation among academic library users.